Antioxidant activities, polyphenolic profile and chemopreventive properties of Cyphomandra betacea L. ethanolic extract on human breast and liver adenocarcinoma cells - Abdul Mutalib, Maisarah (2016)
Cancer is one of the major health problem with one in four Malaysians (1:4) will develop cancer by 75 years old. Increased consumption of fruits and vegetables has been recommended to reduce the risk of various types of cancer. The antioxidant properties of micro and macro nutrients besides the polyphenolic compounds present may explain the protective effects. This study was conducted to investigate the antioxidant activities and anticancer potential of Cyphomandra betacea (tamarillo)and to compare with its counterpart the Solanum lycopersicum (tomato). Results from nutritional compositions analyses showed that tamarillo possessed higher ash, protein, carbohydrate and minerals (calcium, magnesium and potassium) than tomato. Tamarillo also reported to have higher total phenol and flavonoid contents compared to tomato which represents about 7% of its total weight. The antioxidant studies also revealed that tamarillo displayed strongest antioxidant activities as assessed using both DPPH scavenging and beta-carotene bleaching assay. The presence ofp-coumaric acid, caffeic acid and vanillic acid analysed by HPLC have been identified as the key polyphenolic compounds found in tamarillo, meanwhile GC-MS analysis showed the presence of 11 phytochemical compounds. The cytotoxic behavior of tamarillo and tomatoshowed that both extracts strongly inhibited the proliferation of liver (HepG2) and non-hormone dependent breast cancer (MDA-MB-231) cell lines in a dose-dependent manner. Conversely, the sample extracts did not exert any significant cytotoxic effect against 3T3. The cellular morphologyrevealed the typical morphological features of apoptotic cells while AO/PI double staining observed apoptotic mediated cell death of HepG2 and MDA-MB-231. Exposure of both extracts resulted in the formation of DNA ladder pattern in both HepG2 and MDA-MB-231. Tamarillo extract induced cell cycle arrest in HepG2 at sub-G1 phase at 24 h, followed by the reduction in the S and G2/M phases after 72 h of incubation. Further investigations of the antiproliferative activities using colorimetric BrdU incorporation demonstrated a reduction in the number of viable cells which underwent synthesis (S phase), hence suggesting that both extracts demonstrated inhibitory effects in proliferation of HepG2 and MDA-MB-231. Annexin V FIT-C staining confirmed that apoptosis occurred early in HepG2-treated tamarillo while tamarillo treated MDA-MB-231 showed that the early apoptosis increased up to 56% at the end of 48 h of treatment. This apoptosis occurred to be dependent on the activation of caspase-9 and caspase-3, but not caspase-8. Together with the released of cytochrome c, established that both extracts possibly induced apoptosis in HepG2 and MDA-MB-231 through the intrinsic pathway. The molecular mechanism in the induction of apoptosis by both extracts in HepG2 and MDA-MB-231 found that Bax protein was elevated with a concomitant down-regulation of Bcl-2 expression. Alongside, a marked immunoexpression of p53 was also observed. The final chapter concerns the factors that determined the protective roles tamarillo extract on hydrogen peroxide-induced oxidative stress in 3T3. Results showed that cells pre-treated cell with tamarillo extract (10 μg/ml) were best protected from H2O2 toxicity. Also, no toxic effect was observed (200 μg/ml), suggesting that tamarillo is a selective anticancer agent with low toxicity effect. In an attempt to study the combination effect of tamarillo with commercial chemotherapy drug led to final part of this study. Combination of tamarillo extract with Doxorubicin in HepG2 resulted in a synergism effect. The most effective combination (CI values = 0.45) was 1.6 μg/ml of Doxorubicin with 30 μg/ml of tamarillo extract on the growth inhibition of HepG2. In summary, tamarillo demonstrated promising anticancer properties especially in liver and breast cancer that could be attributed for their potent antioxidant activity and high polyphenolic compounds. The synergistic combination of tamarillo with commercial chemotherapy drug opens a new possible approach in the cancer treatments that are more effective and less toxic effect.